Faktor Risiko Hipertensi Pada Lansia Di Wilayah Kerja Puskesmas Kota Banjarmasin - Akhmad Fauzan; Nurul Indah Qariati (HB PRESS, 2018)
Increasing cases of disease not infectious now as hypertension widespread to other places and threatening the quality of life of society especially elderly. The purpose of this research to analyze factors the risks associated with the genesis hypertension in the work area of Puskesmas City Banjarmasin. Target of research is as a input for government agencies in this case health department the city and the province of south kalimantan in the preventive efforts promotional and disease hypertension. A method of in this research survey analytic with an approach case control study .The subject matter of the research is that all the of rheumatoid arthritis cases of hypertension as many as 30 and control as many as 30 of rheumatoid arthritis who do not hypertension .The research instruments used in pt pgn promised to supply tensimeter and questionnaires regarding his habits to take up smoking and physical activity. It is anticipated that analysis data using the test and been approved chi square with the levels of trust 95 %. The results of the chi square between smoking behavior in the hypertension get p = 0,05 ( p = 0,006 ) and value or worth 6,500 ( CI : 95%: 1,820-23,213 ) It means elderly with the behavior smoking had the chance six times greater suffers from hypertension compared with elderly who does not smoke. The results of the chi square between physical activity with the genesis hypertension obtained value p = 0.05 ( p = 0,020 and value or of 4,00 ( CI: 95 %: 1,367-11,703 ). It means elderly with physical activity less than good had the chance 4 times greater suffers from hypertension compared with elderly who physical activity good. The result of this research expected can be used as as one of the inputs to efforts to improve reduction programs hypertension in the health, Particularly in the area of the new town banjarmasin pemurus work as meningkatkam socialization and spreading information such as leaflets , posters etc that all levels of society knows about hypertension.